Consumer self-concept in the cyberspace: how digitization has shaped the way we self-disclose to others - Bartoli, Chiara; Nosi, Costanza; Mattiacci, Alberto; Sfodera, Fabiola (Journal of strategic marketing, 2023)
This study investigates digitization's implications on consumers' self-concept by focusing on how consumers build their self-concept and convey it to others in cyberspace. A systematic literature review (SLR) is undertaken using articles published on this topic in the last twenty years in scholarly business, management, and social science journals. The SLR method has been chosen as it considered as one of the most efficient and high-quality methods to acknowledge extensive literature on a subject, show the body of knowledge, let areas for further research emerge, and unveil the presence of research problems that justify further contribution to the body of existing knowledge. Five major themes characterizing consumer self-concept construction and disclosure online emerge: self-narration in digital spaces, ambivalence between the virtual and real self, digitization and self-enhancement, self and digital possessions, and privacy protection. Based on each topic, future research avenues have been identified. The analysis will help scholars identify some core issues and challenges that require further enquiry. In addition to academics, the analysis can also benefit practitioners who are confronted with a landscape that changes dramatically along with the technological advancements.